IMPLEMENTATION OF MEDIA FLASHCARDS 3 LANGUAGES (ENGLISH-INDONESIA-SAS) IN PROMOTING THE LEARNING OF OTHER LANGUAGES IN CHILDREN AGE - Hidayat, Raka Maypangestu (-, 2024)
Flashcards are small pieces of paper, 25 x 30 cm, that contain interesting pictures and explanations of words that match the pictures in the Flash Card. Flash cards can be said to be visual media that can provide an overview to students about the material being taught and in this study will explain the English language material taught to children in Bintaro Village, Ampenan, Lombok, West Nusa Tenggara. The Flashcard media taught to children contains pictures and words from the picture contained in 3 languages (English, Indonesian, and Sasak). The use of 3 languages in this Flash Card which contains Sasak language as the mother tongue is used to facilitate children's understanding where their mother tongue is Sasak language. The results of student learning show an increase in understanding of basic English learning, namely in cycle I the level of understanding is 35%, Cycle II 50%, Cycle III 67%, Cycle IV 83.3%.